2013
DOI: 10.1007/s12282-013-0492-0
|View full text |Cite
|
Sign up to set email alerts
|

Equol as a potent radiosensitizer in estrogen receptor-positive and -negative human breast cancer cell lines

Abstract: These results suggest for the first time that equol can be considered as a radiosensitizing agent and its effects may be due to increasing cell death following irradiation, increasing the remaining radiation-induced DNA damage and thus reducing the surviving fraction of irradiated cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…For example, in human breast cancer cells and cervical cancer cells, equol elicited the apoptosis pathway through cytochrome c‐mediated caspases cascade (Choi, Ahn, & Bae, ; Kim, Shin, Park, & Kim, ). Recently, it was discovered that equol could be taken as an emerging radio sensitizer due to its excellent capability of enhancing the radiation‐induced apoptosis in breast cancer cells T47D as well as MDA‐MB‐231 (Taghizadeh, Ghavami, Nikoofar, & Goliaei, ). Evidence suggested that equol has the potential to lower the prostate‐specific antigen levels in human prostate cancer cells under 5α‐dihydrotestosterone (5α‐DHT) stimulation and to improve prostate health by reducing serum 5α‐DHT levels and androgen hormone action in Long–Evans rats (Lund et al, ).…”
Section: The Bioactivities and Clinical Applications Of Equolmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in human breast cancer cells and cervical cancer cells, equol elicited the apoptosis pathway through cytochrome c‐mediated caspases cascade (Choi, Ahn, & Bae, ; Kim, Shin, Park, & Kim, ). Recently, it was discovered that equol could be taken as an emerging radio sensitizer due to its excellent capability of enhancing the radiation‐induced apoptosis in breast cancer cells T47D as well as MDA‐MB‐231 (Taghizadeh, Ghavami, Nikoofar, & Goliaei, ). Evidence suggested that equol has the potential to lower the prostate‐specific antigen levels in human prostate cancer cells under 5α‐dihydrotestosterone (5α‐DHT) stimulation and to improve prostate health by reducing serum 5α‐DHT levels and androgen hormone action in Long–Evans rats (Lund et al, ).…”
Section: The Bioactivities and Clinical Applications Of Equolmentioning
confidence: 99%
“…Recently, it was discovered that equol could be taken as an emerging radio sensitizer due to its excellent capability of enhancing the radiation-induced apoptosis in breast cancer cells T47D as well as MDA-MB-231 (Taghizadeh, Ghavami, Nikoofar, & Goliaei, 2015).…”
Section: Antitumormentioning
confidence: 99%
“…Interests in soy isoflavones have been fueled by studies attributing the consumption of soy foods to an increase in metastasis. However, equol, the major metabolite of the soybean isoflavone daidzein, was considered to be a radiosensitizing agent and its effects may be due to increasing DNA damage in two human breast cancer cell lines (T47D and MDA‐MB‐231) . Clinical studies have established that epigallocatechin‐3‐gallate (EGCG), the most abundant catechin in green tea leaves, potentiated efficacy of radiotherapy in breast cancer patients .…”
Section: Sensitization Mechanisms Of Natural Phytochemicals In Breastmentioning
confidence: 99%
“…Radiation response modifier is designed for enhancing apoptosis of cancer cells while having much less effect on normal tissues. To develop modifier, in vitro studies are first step for novel radio-sensitizing agents driving cell death based on biological behavior of cancer cells (Alcorn et al ., 2013; Cho et al ., 2015; Taghizadeh et al ., 2015). In this study, JC3 was evaluated for whether it could be applied to modify radio-resistant breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%